Analysis of (M/G/c): (GD/∞/∞) Menggunakan Software Lazarus - Akbar Maulana; Yuki Novia Nasution; Nanda Arista Rizki (EKSPONENSIAL, 2017)
Queueing theory is a theory that concerns in the mathematical study of queue or row of waiting. The formation of the queue is occurs when the need for a service exceed the capacity of the service. In this study, an analysis is done to determine whether the queue model (M/G/c) :(GD/∞/∞) can be applied to the Workshop of Utomo Motor Yamaha Samarinda Seberang. Primary data is used and is taken for 3 days in a random busy period selected in May to August 2017. The result is the queue system on Utomo Motor Yamaha using FCFS queue discipline with 4 parallel mechanics, and follows the (M/G/4) :(GD/∞/∞) model. The average of the waiting time in the queue on Monday is 0,38 hours and Wednesday is 0,35 hours. The average of the customers in the queue on Monday and Wednesday is the same as much 2 customer. The average of the customers in the system on Monday and Wednesday is the sama as 5 customers. The average of the waiting times that customers spend on the system on Monday is 0,93 hour and Wednesdayis 0,94 hours and on May 22nd, 2017 is 0,81 hours. In order to calculate the queue model more quickly, a program is made using Lazarus software to search the queue model on daily data.